2010
DOI: 10.1007/s10006-010-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous carcinoma of the oral cavity: a clinico-pathologic appraisal of 133 cases in Indians

Abstract: Development of recurrence following radiotherapy in few cases supports anaplastic changes by radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
4
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 30 publications
6
59
4
14
Order By: Relevance
“…When disease recurs, it is almost exclusively local, so negative margins at the time of resection are important [16,17]. In a study of 133 patients with oral cavity VC, Rekha et al [18] reported a local recurrence rate of only 2.3 %. The vast majority of patients were treated with surgery alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When disease recurs, it is almost exclusively local, so negative margins at the time of resection are important [16,17]. In a study of 133 patients with oral cavity VC, Rekha et al [18] reported a local recurrence rate of only 2.3 %. The vast majority of patients were treated with surgery alone.…”
Section: Discussionmentioning
confidence: 99%
“…One of the largest series of oral cavity VC involving 133 patients from India states that ''some cases showed severe degrees of dysplasia and extension into the muscle layer'', however none of their patients showed histologically positive lymph nodes or distant metastases. Local recurrence was seen in only 3 of 133 patients [18]. Another study of 30 cases of laryngeal VC over 23 years showed surgery to be the primary treatment option with concomitant radio/chemotherapy as an alternative for voice preservation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Lesiones similares han sido descritas en sitios como piel, región cérvico-uterina, vejiga, región ano-rectal, región genital y esófago (2,3) . En cavidad bucal se encuentra principalmente en encía, mucosa alveolar y yugal (2) . Presenta mayor predilección por el sexo masculino, en la sexta y séptima década de vida (1,2,3) .…”
Section: Introductionunclassified
“…En cavidad bucal se encuentra principalmente en encía, mucosa alveolar y yugal (2) . Presenta mayor predilección por el sexo masculino, en la sexta y séptima década de vida (1,2,3) . Considerado como un carcinoma con capacidad limitada de invadir y dar metástasis, en cavidad oral el CV representa solamente del 2% al 12% de todas las neoplasias epiteliales.…”
Section: Introductionunclassified
See 1 more Smart Citation